2021
DOI: 10.33448/rsd-v10i10.18996
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity and quality control of a formulation based on Libidibia ferrea after aging

Abstract: This study aimed to evaluate in vitro the pharmacological stability of a herbal mouthwash based on Libidibia ferrea extract after aging, establishing its organoleptic and microbiological characteristics. It is a 7.5% hydroalcoholic extract from Libidibia ferrea pods, using the reflux decoction technique, and spray dried. The stability, pH, sedimentation, density, and antimicrobial activity tests of the mouthwash were performed with the solutions stored after 24 months. Contaminant control was carried out by de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The changes in SOD and GSH activities at different treatment concentrations led to considerably reduced cellular damage ( Figures 5 E and 5 F). This occurs because GSH and SOD consume the formed reactive species ( Souza et al, 2021 ), and it was observed that the activities of SOD and GSH decreased as soon as 3T3 cells underwent oxidative damage. Upon the addition of L. ferrea extract to the exposed cells, we observed that both tested concentrations provided protection against damage, with the highest concentration exhibiting the most significant effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The changes in SOD and GSH activities at different treatment concentrations led to considerably reduced cellular damage ( Figures 5 E and 5 F). This occurs because GSH and SOD consume the formed reactive species ( Souza et al, 2021 ), and it was observed that the activities of SOD and GSH decreased as soon as 3T3 cells underwent oxidative damage. Upon the addition of L. ferrea extract to the exposed cells, we observed that both tested concentrations provided protection against damage, with the highest concentration exhibiting the most significant effect.…”
Section: Discussionmentioning
confidence: 99%
“…S. enterica subsp. enterica serovar Heidelberg “ S. Heidelberg” ( SH ) is a nonspecific host pathogen essential to human health and is characterized by multiple sources of infection and rapid bacterial dissemination ( Souza et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%